An Analysis of Gender Bias in Bilingual Thematic Children’s Picture Storybooks - Aulliah, Novyko Dwi; Maisarah, Ira (UNIB Press, 2023)
Childhood is a period of forming the basic character of every human being, in which basic knowledge about life and living becomes the main goal of the educational process. Various literary works can be used as teaching materials, including those contained in picture story books which can be easily accessed by everyone. However, not only children's storybooks but the textbooks used in schools also show a lot of gender inequality. The purpose of this research was to analyze the gender bias in bilingual thematic children's picture storybooks. The present study used a qualitative design. The researcher analyzed gender from the pictures and text contained in these thematic storybooks. This research discovered bias in gender both in the picture and in texts of storybooks